MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MULTIMEDIA PADA SISWA BERKESULITAN BELAJAR MEMBACA KELAS 1 SDN O5 BATU TABA KAB. AGAM - Zulfitri - (Universitas Negeri Padang, 2014)
Abstrack: The study begins with the problems that the researcher found at the first grade in SDN 05 Batu taba, Kab. Agam, in Indonesian language subject. Especially in learning to read, learning to read in child has a problem in arranging the letters into syllables and syllables into words. This research method was experiment research with single subject research (SSR) that used A-B design. The result of the research conducted 16 times of observations with two conditions. The first baseline condition that made as much as 8 times of the observations shows the result was 10%-20%. With the analysis of condition, the tendency toward increase (+) the tendency of the stability of 0%, and 10% change level conditions of interventions through Multimedia as much as 8 times of observation which shows the results 40%-80%. With the analysis of the baseline conditions, the trend towards increased baseline condition (+) 0% trend of stabilities and change to level 10 %. The trend toward increase state intervention (+) 25% trend of stabilities and change level to 40%. And analysis of the conditions was change tendency of stable variation to varias, change level 20% and 0% overlap. Thus, it is evident that multimedia can improved the beginning reading ability at of the difficulty of learning to read X class at the first grade in SDN 05 Batu taba, kab. Agam Kata kunci: Multimedia; Kemampuan Membaca Permulaan.